2017
DOI: 10.1016/j.econlet.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Volatility estimation for Bitcoin: A comparison of GARCH models

Abstract: Bitcoin is undoubtedly the most popular cryptocurrency. Earlier studies have found that Bitcoin is mainly used as an asset, and hence analysing its volatility is of great importance. In this article, we explore the optimal conditional heteroskedasticity model with regards to goodness-of-fit to the data. It is found that the best conditional heteroskedasticity model is the AR-CGARCH model, highlighting the significance of including both a short-run and a long-run component of the conditional variance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
489
0
24

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 878 publications
(539 citation statements)
references
References 7 publications
26
489
0
24
Order By: Relevance
“…The results are interesting to note. There are not large differences among the GARCH models, however, CGARCH model is the most appropriate model among the GARCH models judging from the Akaike Information Criteria (AIC) and Hanna-Quinn Criteria (HQ), which are similar to results discussed in Katsimpa (2017) and Bouoiyour and Selmi (2015). When examining the Bitcoin's prices, traders should see the volatilities, the short-run changes in volatility, and the long-run changes of volatility.…”
Section: Garch Modelsupporting
confidence: 72%
“…The results are interesting to note. There are not large differences among the GARCH models, however, CGARCH model is the most appropriate model among the GARCH models judging from the Akaike Information Criteria (AIC) and Hanna-Quinn Criteria (HQ), which are similar to results discussed in Katsimpa (2017) and Bouoiyour and Selmi (2015). When examining the Bitcoin's prices, traders should see the volatilities, the short-run changes in volatility, and the long-run changes of volatility.…”
Section: Garch Modelsupporting
confidence: 72%
“…Unlike Urquhart (2016) and Nadarajah and Chu (2017) use transformed Bitcoin returns and report evidence of market efficiency. Katsiampa (2017) focuses on the price volatility of Bitcoin and explores the optimal conditional variance model. Furthermore, Urquhart (2017) finds evidence of price clustering at round numbers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, Urquhart (2017) finds evidence of price clustering at round numbers. Katsiampa (2017) focuses on the price volatility of Bitcoin and explores the optimal conditional variance model. Bouri, Azzi, and Dyhrberg (2017) report evidence of a negative relation between the U.S. implied volatility index and Bitcoin volatility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dyhrberg (2016b) explored the financial asset capabilities of Bitcoin using GARCH models and showed several similarities to gold and the dollar indicating hedging capabilities and advantages as a medium of exchange. Katsiampa (2017) explored the optimal conditional heteroscedasticity model with regards to goodness-of-fit to Bitcoin price data, and found that the best model is the AR-CGARCH model, indicating significance of including both a short-run and a long-run component of the conditional variance. Urquhart (2017) examined the volatility of Bitcoin as well as shedding light on the forecasting ability of GARCH models and heterogeneous auto-regressive (HAR) models in the Bitcoin market.…”
Section: Literature Reviewmentioning
confidence: 99%